The impact of hiring top workers on productivity: what is the role of absorptive capacity?. Issue 20 (28th November 2018) - Lodefalk, Magnus; Tang, Aili
ABSTRACT: We examine the heterogeneous productivity impacts of hiring top workers on small and medium-sized enterprises, exploiting matched employer–employee panel data and employing within-firm as well as matching and difference-in-difference estimators. The results provide robust evidence that the productivity impact is stronger for firms with higher absorptive capacity. Technological laggards within an industry benefit more strongly from hiring top workers if their workforce is more well-educated.